Clinical Practice Guidelines for Pre-eclampsia and Eclampsia Treatment. - Frank Carlos Alvarez Li; Carlos Zerquera Alvarez; Moisés Aramis Santos Peña; Pedro Nieto Prendes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Pre-eclampsia and Eclampsia Treatment. This disease is part of a group of conditions known as hypertensive disease in pregnancy that have in common the existence of high blood pressure. This document includes a review and update of the main clinical aspects, concepts, classification and treatment stressing the use of drugs that cause hypotension and magnesium sulphate. It includes assessment guidelines focused on the most important aspects to be accomplished.